2017
DOI: 10.5194/essd-2017-79
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EDGAR v4.3.2 Global Atlas of the three major Greenhouse Gas Emissions for the period 1970–2012

Abstract: 2 use, land-use change and forestry (LULUCF) sector (including forest and savannah burning). Unlike the activities of the LULUCF sector, which are typically estimated top-down from less certain land-use observations, all these activities are estimated bottom-up from standard annual statistics of fuel, products, waste, crops or livestock. We present country-specific emission totals and analyse the trends and variations in emissions of the largest emitting countries together with the EU in more detail, to uncove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
124
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(126 citation statements)
references
References 16 publications
(17 reference statements)
1
124
0
1
Order By: Relevance
“…lower clinker ratios) in cement production in response to work by the World Business Council for Sustainable Development (WBCSD), who released sample-based estimates of the clinker ratio in a range of countries (Anonymous, 2010). In version 4.3.2, EDGAR used official estimates from Annex I parties to the UNFCCC, specific clinker R. M. Andrew: Global CO 2 emissions from cement production 197 production data for China, and the WBCSD database for all remaining countries (Olivier et al, 2016;Janssens-Maenhout et al, 2017). Since 2003, countries that are listed in Annex 1 of the UN Framework Convention on Climate Change (UN-FCCC) have been required to submit annual inventories of greenhouse gas emissions in considerable detail, including estimates of emissions from cement production (UNFCCC, 2017).…”
Section: Previous Estimates Of Global Cement Emissionsmentioning
confidence: 99%
“…lower clinker ratios) in cement production in response to work by the World Business Council for Sustainable Development (WBCSD), who released sample-based estimates of the clinker ratio in a range of countries (Anonymous, 2010). In version 4.3.2, EDGAR used official estimates from Annex I parties to the UNFCCC, specific clinker R. M. Andrew: Global CO 2 emissions from cement production 197 production data for China, and the WBCSD database for all remaining countries (Olivier et al, 2016;Janssens-Maenhout et al, 2017). Since 2003, countries that are listed in Annex 1 of the UN Framework Convention on Climate Change (UN-FCCC) have been required to submit annual inventories of greenhouse gas emissions in considerable detail, including estimates of emissions from cement production (UNFCCC, 2017).…”
Section: Previous Estimates Of Global Cement Emissionsmentioning
confidence: 99%
“…reported that global total CH 4 emissions were estimated at 558 Tg/year, of which about 60% were originated from anthropogenic sources such as agricultural production and fossil fuel extraction. Recent bottom-up inventories have shown the rapid rise in anthropogenic CH 4 emissions since 2000 (Höglund-Isaksson, 2017;Janssens-Maenhout et al, 2017;Olivier et al, 2017;Rice et al, 2016;, especially in some developing countries such as China. To reduce the uncertainties in future climate projections, worldwide researchers have focused on the inventories of CH 4 emissions and corresponding mitigation strategies at various scales from regional to global (e.g., Crill & Thornton, 2017;Schaefer et al, 2016;Schwietzke et al, 2016;B.…”
Section: Introductionmentioning
confidence: 99%
“…Production-based emission accounting (PBA) represents the on-site emissions within national territory (sometimes referred to as territorial-based) preferred by the UNFCCC. Existing studies whether regarding national, regional, and sectoral CH 4 emissions are all in the scope of PBA circumstance (e.g., Du et al, 2018;Höglund-Isaksson, 2017;Hopkins et al, 2016;Janssens-Maenhout et al, 2017;B. Zhang, Chen, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Further details on activity data by sector can be found in Janssens- Maenhout et al (2017) and in Sect. S4 in the Supplement.…”
Section: Revised Total Nmvoc Emissions Of Edgarmentioning
confidence: 99%